Emergency hepatectomy for hepatic arteriovenous malformation combined with pulmonary hypertension in an infant - Naruhiko Murase; Hiroo Uchida; Akihide Tanano; Chiyoe Shirota; Akinari Hinoki; Takahisa Tainaka; Kazuki Yokota; Kazuo Oshima; Ryo Shirotsuki (Elsevier, 2015)
Patients with hepatic arteriovenous malformations rarely present with pulmonary hypertension. We report the case of a 3-month-old boy who developed severe pulmonary hypertension due to a hepatic arteriovenous malformation. The use of pulmonary vasodilators to treat the patient's pulmonary hypertension worsened his high-output heart failure. This is the first case in which emergency hepatectomy rescued a patient with hepatic arteriovenous malformations who developed pulmonary hypertension.